2007
DOI: 10.1126/science.1139892
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Induced Sudden Death of Entanglement

Abstract: We demonstrate the difference between local, single-particle dynamics and global dynamics of entangled quantum systems coupled to independent environments. Using an all-optical experimental setup, we showed that, even when the environment-induced decay of each system is asymptotic, quantum entanglement may suddenly disappear. This "sudden death" constitutes yet another distinct and counterintuitive trait of entanglement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
765
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 922 publications
(783 citation statements)
references
References 16 publications
11
765
0
7
Order By: Relevance
“…We can draw two important conclusions from the result in equation (3). First, C r is always larger than C d , which means that weak measurement and quantum measurement reversal indeed can be used for protecting entanglement from decoherence.…”
mentioning
confidence: 89%
“…We can draw two important conclusions from the result in equation (3). First, C r is always larger than C d , which means that weak measurement and quantum measurement reversal indeed can be used for protecting entanglement from decoherence.…”
mentioning
confidence: 89%
“…This signifies a "sudden death of (non-local) entanglement" whereas the decay characteristics of local decoherence is exponential. Finite-time disentanglement has also been observed in a recent experiment [16]. In the following we study the disentanglement of the state ρ cav,f .…”
Section: Finite-time Disentanglementmentioning
confidence: 93%
“…For the non-trivial class of states discussed here, this can even occur during finite time. This phenomena of "sudden death of entanglement" has been investigated theo-retically for a conventional cavity QED setup [15] and observed in an experiment as well [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in some cases entanglement can completely disappear in finite times. This phenomenon is known as entanglement sudden death (ESD) [7][8][9][10] and has been observed experimentally by Almeida et al [11]. It is of clear relevance to study and understand ESD and related phenomena occurring during the evolution of open quantum systems, because the actual implementation of quantum computation and other quantum information tasks depend on the longevity of entanglement in multiqubits states.…”
Section: Introductionmentioning
confidence: 99%